A Framework for Measuring The Effect of Changeover Time To Overall Equipment Effectiveness - Muhamad Arifpin, Mansor; A. R., Ismail; Mohamad R., M. Yasin; A., Halim (Universiti Malaysia Pahang, 2015)
Single Minutes of Exchange Die (SMED), developed by Shigeo Shingo is an approach to improve changeover of die by reduction its setup time. Longer setup time will lead to shorter Availability in Overall Equipment Effectiveness (OEE), thus will give effect to the actual time of production. For this reason, a study need to be conducted to measure how the performance of setup or changeover process effect the Availability in OEE. This paper propose a framework on how to measure the effect of changeover time to OEE by using Data Envelopment Analysis (DEA). The study benchmark Single Minutes of Exchange Die process in the same production line dynamically. The manpower and the external setup time are the main inputs in this measuring process where the main output is the Availability of OEE. This framework can be used to determine the efficiency of converting internal setup time to external setup time. An efficient converting process from internal setup time to external setup time will give a good effect to the Availability and thus contribute to the longer production time.